Gabbro Discovery in Discovery Deep: First Plutonic Rock Samples From the Red Sea Rift Axis - Follmann, Jörg; van der Zwan, Froukje M.; Preine, Jonas; Hübscher, Christian; Bousquet, Romain; Augustin, Nico (Frontiers in Earth Science, 2021)
Plutonic rocks such as gabbros provide information on magmatic and tectonic processes occurring beneath a mid-ocean rift axis and on the formation of the oceanic crust. Igneous rocks, reported from the Red Sea Rift valley so far, had been limited to extrusive basalts. The only deeper crustal rocks found in the Red Sea area are from the rift flanks, interpreted as late-stage continental rift magmatism. Here, we present the geochemistry of the first recovered gabbro fragments from the axis of the Red Sea Rift, sampled from a crater structure within the brine-filled Discovery Deep. Petrology and geochemistry show characteristics of a typical mid-ocean ridge gabbro formed at shallow crystallization depth. Clinopyroxene core mineral data fall within two groups, pointing to a multiphased magmatic history, including different magma batches and a joint late-stage fractional crystallization. Geobarometry, based on clinopyroxene cores suggests lower crystallization pressures than similar geobarometric data reported for gabbroic samples from Zabargad (8–9 kbar) and Brother's Islands (2.5–3.5 kbar) from the rift flanks. However, based on the evolved whole rock composition, its multiphase history, the thickness of the crust, the current location of the samples, and the uncertainties in the barometer, geobarometric estimates for the samples are likely overestimated. Instead, we propose that these rock fragments originate from the upper part of a fully developed oceanic crust in the central Red Sea Rift. High-resolution bathymetry and sparker seismic data reveal that the Discovery Deep is characterized by a significant normal fault and a strong reflector near the rift axis, which we interpret as a potential sill intrusion in an approximate depth of 400 m. Based on the lack of progressive alteration and the sampling location within a sediment-free crater structure, we interpret the emplacement of the gabbros has to be geologically recent. We interpret the gabbro either as a xenolith in the eruptive volcanism that formed the crater, potentially related to the sill intrusion visible at depth. Alternatively, the intrusive gabbro was uplifted and deposited in a talus fan by the adjacent normal fault, exposed of overlaying sediments by the formation of the volcanic crater.